Designing the memory of terror, negotiating national memory: The National September 11 Memorial and the National Memorial for Peace and Justice. (June 2023) - Sturken, Marita
This essay analyzes two American memorials that were built in the post-9/11 era: the National September 11 Memorial in New York City, which opened in 2011, and the National Memorial for Peace and Justice, which opened in Montgomery, Alabama, in 2018. Both of these memorials pay tribute to victims of terrorism, the first to victims of foreign terrorism and the second to victims of lynchings, a form of racial terrorism within the United States. This essay argues that these two memorials define the beginning and end of the post-9/11 era, from memorialization as a nationalist enterprise to memorialization as a reckoning on race that demands the destruction of racist monuments and the construction of memorials to victims of racist violence. It looks in particular at how the modern designs of these two memorials produce very different kinds of experiences of memory to tell distinct narratives of victimhood, loss, and nation.